Alcohol Calculations in Emergency and Forensic Medicine - John Brick; William Bennett (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2017)
In emergency medicine, the most common legal drug encountered worldwide is ethanol (alcohol). Alcohol is consumed by a large portion of people in most countries. The harmful and hazardous consequences of acute alcohol intoxication are an international problem and a significant contributing factor to injuries and death. About 20% of emergency department admissions involve alcohol [1], and overall, alcohol is a direct or indirect cause of approximately half of all intentional and unintentional injuries resulting in death [1,2]. Non- quantitative clinical tools to assess intoxication may include casual observation (e.g., odor of alcoholic beverage, behavioral disturbances), which may lead to screening, brief interventions, referral and treatment (SBIRT). In some instances, a method to make quantitative estimates of intoxication based upon pre-admission patient history may be useful and often of clinical and medicolegal value. For  example, estimating the blood alcohol concentration (BAC) in overdose patients based on reported alcohol intake may be required to assist in a diagnosis or medication treatment plan before a chemical test is available or in estimating when a patient will be sober enough to ethically be released from the ED. This is particularly important because clinical signs of intoxication are not reliably observed at lower BACs [3-5], even though impairment and risk for further injury may be signifi cant [6]. In hospitals, chemical testing using clinical (e.g., ADH method) or other methods (e.g., breath testing, gas chromatography), while objective, only provide an objective result at the time the sample is obtained.